Effect of Diet Program on Upper Arm Circumference - Istiqomah, Istiqomah; Marswita, Rino Arianto; Nabila, Istiqomah Syarifah (Smart Medical Journal, 2022)
Introduction: As time goes by, lifestyle is changing. The imbalance of energy intake and energy expenditure will result in underfeeding or overfeeding. Police officers at Polresta Depok are obese about 34,6 %. This research is the first research to investigate the effect of the diet program with Mid-Upper Arm Circumference on Policemen at Bhayangkara Prof. Dr. Awaloedin Djamin hospital in Semarang City. Methods: The design of this study is one group pre-test and post-test design with inclusion criteria that are Policemen with BMI >30 and willing to take part in this study. The exclusion criteria are having a history of medullary thyroid carcinoma. The data collected in this study used consecutive sampling. The statistical analysis used a nonparametric Wilcoxon test.Results: Mid-Upper Arm Circumference mean before and after intervention were 36,8 ± 5,72 and 38,9 ± 3,22 with Asymp. Sig. (2 - tailed) p= <0,001. (p<0,05). Thus, the effect of a diet program with Mid-Upper Arm Circumference is significant.Conclusion: A diet program, consisting of liraglutide injection, diet food, and exercise, has a significant effect on Mid-Upper Arm Circumference.